Two copper(II) compounds derived from tetrazole carboxylates for chemodynamic therapy against hepatocellular carcinoma cells - Shi, Xinya; Gu, Yulan; Wan, Chuandan; Jiang, Xin; Shen, Lei; Tan, Litao; Zhong, Yujie; Zou, Dengfeng (Frontiers in Chemistry, 2022)
Two Cu(II) compounds based on tetrazole-carboxylate ligands, [Cu(phtza)2(H2O)2]∙3H2O (1), [Cu(atzipa)2]∙2H2O (2) (phtza = 2,2'-(5,5'-(1,3-phenylene)bis(2H-tetrazole-5,2-diyl))diacetate, atzipa = 3-(5-amino-1H-tetrazol-1-yl)isopropanoic anion) were designed and synthesized by hydrothermal reactions. The X-ray diffraction results shows that the two compounds show two dimensional (2D) layer structures. Nanoprecipitation with DSPE-PEG-2000 contributes to the formation of the nanoparticles (NPs) with excellent water dispersity. In vitro study indicates that the two NPs exerts considerable cytotoxicity towards human hepatocellular carcinoma cell (HepG2 and Huh7) with low half maximum inhibitory concentration (IC50). The cytotoxicity of these NPs was also investigated by the flow cytometry and Calcein-AM/PI (live/dead) co-stained experiments. The results promise the great potential of these NPs for chemodynamic therapy against cancer cells.